Poetry of Comparison between Tlemcen and Fez: The Poems of Al-Thughri al-Tlemcani and Mandil ibn Ajurrum as a Case Study - Qibouj, Abdelaziz (El Omda in Linguistics and Discourse Analysis, 2023)
The poetry of describing cities and urban centers represents a phenomenon worthy of research and study, due to the civilizational, cultural, and historical dimensions it encompasses, in addition to its artistic aspect. Poets of the Maghreb have celebrated their cities and urban centers, leaving behind a rich corpus of poetry praising cities and expressing deep attachment to them. Some cities received significant attention from poets, notably Tlemcen and Fez. In this study, we have chosen to conduct a comparative artistic analysis between the two cities, Tlemcen and Fez, through the poems of Al-Thughri al-Tlemcani and Mandil ibn Ajurrum, which engage in a poetic comparison between the two cities. Our aim is to highlight the artistic and aesthetic features of both texts, drawing on the prevailing poetic traditions in the Maghreb and al-Andalus during that period.